Role of serum sodium levels in recurrence and recurrent episodes of febrile seizure - Benny, Sara (International Journal of Contemporary Pediatrics, 2020)
Background: Simple febrile seizures are the common childhood seizures, usually affecting 1 in 20 children between the age group of 6 months to 60 months. Earlier studies have shown an association between low serum sodium as a cause for febrile seizures and its recurrences. The present study was to determine the role of serum sodium in predicting febrile seizure recurrence within 24 hrs and recurrent episodes. Methods: Children aged between 6 months to 60 months with first episode of febrile seizures, admitted to the Paediatric ward of MOSC medical college Kolenchery, were recruited in the study. Inclusion criteria were demographic data, family history, clinical examinations, and laboratory investigations (serum sodium and hemoglobin). Results: Of the total study population of 100 children 33 had recurrences in 24 hours and 16 had recurrent episodes. About 57 children had a family history of febrile seizures, out which 28 children had recurrence of febrile seizure within 24 hours. 26 children had family history of epilepsy, of which only 8 had recurrences in 24 hours and 5 had recurrent episodes. Serum sodium levels of 69 children was above 130 mmol/l and 31 children had sodium level below 130mmol/l. Of 31 children, with low serum sodium levels (<130mmol/l), 29 had recurrence within 24 hours, which was not statistically significant. The sodium levels of 16 children who had recurrent episodes of seizure, was also between 130.1-135mmol/. No significant differences were seen between the serum sodium levels in simple febrile seizures and recurrent episodes. Conclusions: Study showed low serum sodium is not statistically significant to predict a recurrence within 24 hours, but a relative hyponatremia can predispose, a febrile child to occurrence of simple febrile seizure.